Paraguay : Integrated Fiduciary Assessment - World Bank (Washington, DC, 2012)
This Integrated Fiduciary Assessment (IFA) for Paraguay is an exercise in which the Government convened its development partners, including the World Bank (WB), Inter-American Development Bank (IDB), and the European Commission (EC) in a consultative process designed to establish an agenda on Public Financial Management (PFM) and Procurement (PR), and other related governance aspects. It is expected that this process will contribute to: i) identify key PFM & PR strengths and weaknesses of the central government of Paraguay, including those related to the management and implementation of the foreign financed (through grants and loans) public investment programs; and ii) prepare an action plan to guide future efforts in PFM and PR for all central government spending. Paraguay has made important progress in a number of governance areas in recent years. The World Bank Institute (WBI) governance indicators show some progress during the last decade. It is also seen that public services are being delivered more effectively, including in what attains to PFM and PR. Nevertheless, important challenges still remain, particularly in the area of curving down corruption. Paraguay ranked 111 out of 163 countries in transparency international's 2006 survey. The purpose of the IFA is to assess PFM and PR performance in Paraguay. It acknowledges the governance context and the corruption in particular, which affects both the PFM and PR but does not analyze them per se.